Understanding an elementary school teachers' journey of using technology in the classroom from sand table to ınteractive whiteboard - Ali Ersoy; Mahmut Bozkurt (International Electronic Journal of Elementary Education, 2015)
The aim of this study is to understand an elementary teachers’ experiences about using interactive whiteboard (IWB) in the classroom. Narrative inquiry were adopted to conduct the study. The data were collected through semi-structured interviews with the teacher and analysed through narrative analysis. In the study, two major stories emerged. The first story was about the characteristics and difficulties of being an innovative and transformative teacher. In the second story, the use of technology in the classroom were cited. Second story consisted of such sub-stories as changing student profiles, teaching-learning process, measurement and evaluation process, infrastructural adequacy, stakeholder interaction, facilitator role of the technology and challenges of using IWB in the classroom. In all these stories, the examples and advantages of effective use of IWB in the classroom were explained. We can have the following suggestions from the words of the classroom teacher who has been using various technological tools in his classroom for about 40 years, including 10-year IWB use: Teachers should be open-minded for innovation in the sense of professional development, consider the interests of students, reduce the prejudice about the use of technology, utilize the processes that increase and facilitate the learning.